Insights into circular RNAs: their biogenesis, detection, and emerging role in cardiovascular disease. Issue 12 (2nd December 2021) - Ward, Zoe; Pearson, John; Schmeier, Sebastian; Cameron, Vicky; Pilbrow, Anna
ABSTRACT: Circular RNAs (circRNAs) are an evolutionarily conserved form of noncoding RNA with covalently closed loop structures. Initial studies established a functional role for circRNAs as potent microRNA sponges and many other studies have focussed solely on this. However, the biological functions of most circRNAs are still undetermined and other functional roles are gaining traction. These include protein sponges and regulators, and coding for proteins with an alternative mechanism of translation, potentially opening up a whole new transcriptome. The first step to gaining insight into circRNA function is accurate identification and various software platforms have been developed. Specialized detection software has now evolved into whole bioinformatics pipelines that can be used for detection, de novo identification, functional prediction, and validation of circRNAs. However, few cardiovascular circRNA studies have utilized these tools. This review summarizes current knowledge of circRNA biogenesis, bioinformatic detection tools and the emerging role of circRNAs in cardiovascular disease.